2020
DOI: 10.1101/2020.11.25.397422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Istaroxime treatment ameliorates calcium dysregulation in a zebrafish model for Phospholamban R14del cardiomyopathy

Abstract: The heterozygous phospholamban (PLN) p.Arg14del (R14del) mutation is found in patients with dilated or arrhythmogenic cardiomyopathy. The PLN R14del mutation triggers cardiac contractile dysfunction and arrhythmogenesis by affecting intracellular Ca2+ dynamics. Little is known about the physiological processes preceding PLN R14del induced cardiomyopathy, which is characterized by sub-epicardial accumulation of fibrofatty tissue, and a specific drug treatment is currently lacking. Here, we addressed these issue… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…GO term analysis did not identify overrepresentation of any terms in either gene set (false discovery rate <0.05). However, among the downregulated transcripts, we found three well-characterized myocardial genes including phospholamban ( pln/plna ), 63,64 atrial myosin heavy chain 6 ( myh6 ), 65 and natriuretic peptide precursor a ([ nppa ] 66,67 ; Figure S8B; Table S3). We documented trending downregulation of nppa by reverse-transcription quantitative PCR (RT-qPCR) at 33 hpf (Figure S7C).…”
Section: Resultsmentioning
confidence: 99%
“…GO term analysis did not identify overrepresentation of any terms in either gene set (false discovery rate <0.05). However, among the downregulated transcripts, we found three well-characterized myocardial genes including phospholamban ( pln/plna ), 63,64 atrial myosin heavy chain 6 ( myh6 ), 65 and natriuretic peptide precursor a ([ nppa ] 66,67 ; Figure S8B; Table S3). We documented trending downregulation of nppa by reverse-transcription quantitative PCR (RT-qPCR) at 33 hpf (Figure S7C).…”
Section: Resultsmentioning
confidence: 99%
“…At the molecular level, they report a first critical difference between istaroxime and PST3093, given that PST3093 does not inhibit the Na 1 /K 1 ATPase pump but only stimulates SERCA2a, thus qualifying PST3093 as a selective activator (Arici et al, 2022). In addition, they revealed that PST3093 acts by weakening the SERCA-PLN interaction, a mechanism that had been previously confirmed, although not in an exclusive manner (Racioppi et al, 2021), also for istaroxime (Ferrandi et al, 2013;Kamel et al, 2021). Importantly, the authors were able to assess the pharmacokinetics of PST3093 in patients with HF, measuring a half-life of approximately 9 hours, substantially longer than that of istaroxime (Arici et al, 2022).…”
mentioning
confidence: 75%
“…Previous studies have shown computational evidence and suggestive experimental evidence in other organisms. In Zebrafish, the plna R14del variant causes beat-to-beat variations in cardiac output in the absence of cardiac remodeling, suggesting that the cardiac contractile dysfunction is not caused by but rather causal for cardiac remodeling [36]. Causal relationships between anomalies in the QRS complex, specifically in the Q-R upslope, and increased risk of DCM have been found through the Mendelian randomization approach using genetic variants of ECG signatures [37].…”
Section: Discussionmentioning
confidence: 99%